Characterization of the Pathology, Biochemistry, and Immune Response in Kunming (KM) Mice Following Fasciola gigantica Infection - Mei, Xuefang; Zhang, Yaoyao; Quan, Chenyu; Liang, Yiying; Huang, Weiyi; Shi, Wei (Frontiers in Cellular and Infection Microbiology, 2022)
As a putative model of Fasciola gigantica infection, detailed data in Kunming (KM) mice infected with F. gigantica are lacking. In this study, KM mice were orally infected with 15 metacercaria for 8 weeks. Macroscopic and microscopic changes, serum biochemistry, cytokine responses, and changes in parasite-specific immunoglobulin G (IgG) antibody levels were monitored at 1, 3, 5, 7, and 8 weeks post-infection (wpi), respectively. The serum levels of aspartate aminotransferase (AST) and alanine aminotransferase (ALT) increased after infection, while that of albumin (ALB) decreased, which was positively correlated with the degree of liver damage. Between 5 and 7 wpi, the mice showed symptoms of anemia and weight loss, possibly caused by the decrease of alkaline phosphatase (ALP). Moreover, the changing tendencies of the levels of globulin (GLB) and parasite-specific IgG antibody were similar, suggesting a potential correlation between GLB production and adaptive immune response in the host. Coordinated variations in interferon gamma (IFN-γ) and interleukin 4 (IL-4) indicated a mixed T helper 1 (Th1)/Th2 cellular immune response. Furthermore, the serum IgG antibody increased after infection and peaked at 5 wpi, and it was positively correlated with the average parasite burdens. The worms collected from mice were approximately 1 cm in length at 8 wpi, their digestive and reproductive systems were well developed, and no eggs were found in the uterus. To the best of our knowledge, this is the first report describing detailed histological, biochemical, and immunological indices in KM mice infected with F. gigantica, which provides basic information on KM mice against infection with F. gigantica.